Security Enhancement via Device-to-Device Communication in Cellular Networks - Wang, Jiaheng; Tang, Qi; Yang, Chungang; Schober, Robert; Li, Jing (IEEE Signal Processing Letters, 2016)
Device-to-device (D2D) communication underlaying cellular networks improves spectral efficiency but causes interference to cellular users (CUs). Such interference can be utilized to help CUs prevent wiretapping. This paper aims to achieve the twofold goal of security provisioning for CUs and spectral efficiency enhancement for D2D links by optimizing the resource sharing of CUs and D2D links. We first provide the necessary and sufficient conditions for the accessibility of a CU channel by a D2D link. Then, we derive the jointly optimal resource sharing strategy, including the closed-form power control and the optimal channel pairing of CUs and D2D links. Numerical results show that the proposed strategy can improve both the CUs' security and D2D spectral efficiency.<br
Keywords: Device-to-device communication; Copper; Security; Power Control; Quality of Service; Interference; Resource management